Performance evaluation and mathematical analysis of direct sequence and frequency hopping spread spectrum systems under wideband interference - Fawzan Ghalib Abdul Karim Bawahab; Edi Kurniawan; Elvan Yuniarti; Bambang Widiyatmoko; Dwi Bayuwati (International Journal of Advances in Intelligent Informatics, 2018)
This paper presents performance evaluation and comparison analysis of Direct Sequence Spread Spectrum (DSSS) and Frequency Hopping Spread Spectrum (FHSS) systems. The evaluation and analysis are done based on the systems performance against wideband interferences. The interferences are signals with similar spectrum characteristic to the transmitted signals of DSSS and FHSS systems. Bit Error Ratio (BER) is used as evaluation parameter to assess the performance of both systems. Simulation and mathematical analysis are performed to test and verify the performance of both systems. Mathematical analysis also verifies that increasing Spreading Frequency on certain conditions will reduce the BER. This research also points out that FHSS system has a better performance compared to DSSS system indicated by smaller BER.